Raised Plasma Neurofilament Light Protein Levels After Rewarming Are Associated With Adverse Neurodevelopmental Outcomes in Newborns After Therapeutic Hypothermia - Shah, Divyen K.; Yip, Ping K.; Barlas, Akif; Tharmapoopathy, Pavithira; Ponnusamy, Vennila; Michael-Titus, Adina T.; Chisholm, Philippa (Frontiers in Neurology, 2020)
Aim To determine the predictive value of plasma neurofilament light protein (NfL) as a prognostic marker for outcomes in babies who have undergone therapeutic hypothermia (TH) for hypoxic ischemic encephalopathy. Method NfL levels from three groups of term newborns were compared; 1) those with mild HIE who did not receive TH, 2) newborns treated with TH who had minimal or no brain injury on MRI and 3) newborns treated with TH who had substantial brain injury on MRI. Follow-up outcomes were collected from 18 months onwards. Results Follow-up was available for 33/37 (89%) of children. A cut-off NfL level >436 pg/ml after rewarming (median age 98 hours) was associated with adverse outcome with a diagnostic sensitivity 75%, specificity 77%, PPV 75% and NPV 77%. NfL levels at earlier time points were not predictive of outcome. Interpretation This pilot study shows that persistently raised plasma NfL levels after rewarming are associated with adverse outcomes in babies with HIE who have undergone TH.